Impact of National Training on Sorghum Cultivation for Value-addition - Rajendra R Chapke , VR Bhagwat; JV Patil (Indian Journal of Extension Education, 2015)
The study was conducted at Directorate of Sorghum Research, Hyderabad on 20 trainees comprising of agriculture officers from four state agricultural departments engaged in field extension to assess impact of the training programme conducted on sorghum value-added products and sweet sorghum. The data were collected through direct interactions with the participants and interview schedule . Results revealed that the learning index of the trainees was significantly correlated with their age, job experience, and level of satisfaction about training materials and atmosphere. Before training, majority of them (60%) belonged to medium knowledge level (between 16 and 30 knowledge score) who had more than double knowledge score (49-84) after the training. Knowledge gained was found to be highly significant at 0.001% level. The topics viz., improved package of practices for kharif and rabi sorghum cultivation followed by approaches for transfer of improved sorghum technologies, sweet sorghum as versatile bio-energy crop, major weeds of sorghum and their management and value-addition to sorghum with reference to its industrial uses and entrepreneurship development were perceived as more useful. The overall impact on the trainees was found to be highly significant and encouraging. This course will help them in their job to organize effective extension programmes and encourage small entrepreneurs at grass root level.